Reconstruction of vegetation cover and land use ca. 1550 and their change towards 2007 in the Valdivian Rainforest Ecoregion of Chile (35º – 43º 30´ S) - Lara, Antonio; Solari, María Eugenia; Prieto, María Del Rosario; Peña, María Paz (Bosque (Valdivia), 2017)
The estimation of the forest and vegetation cover in the Valdivian Rainforest Eco-region (35º - 43º30´ S) of Chile in the Pre-European period emerges as a relevant scientific question due to its implications for forest conservation and for the improvement of the understanding of the patterns and dynamics of human settlement. This study uses a transdisciplinary approach integrating information from historical documents, archaeological evidence and the relationship of present vegetation with environmental variables. From this analysis we developed the first reconstruction of the forest and vegetation in the Valdivian Rainforest Eco-region circa 1550 (1:500.000 scale map). Our results indicate that native forests covered 11.3 million ha ca. 1550 at the Spanish conqueror arrival, decreasing to 5.7 million ha in 2007 (50.4 % of the original area). This reduction is due to the conversion of native forests to pasturelands, shrublands and agriculture land and, since 1974, forest plantations of exotic species. This study shows the need to continue developing transdisciplinary research, which integrates historical, archaeological and biophysical (potential vegetation, pollen analysis and dendrochronology) data to improve the understanding of changing forest and vegetation cover under climatic fluctuations and human influences during the last 450 years.